Pengaruh Film Kartun Upin & Ipin Terhadap Moral Pada Anak Usia 5-6 Tahun Di TK Tunas Jaya - Ayu Ariska; Bukman Lian; Santa Idayana Sinaga (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The aim of this research is to determine the effect of the Upin & Ipin cartoon film on morale in children aged 5-6 years in Tuna Jaya Kindergarten. Background Moral development in children is the child's behavior and good behavior, namely honesty, tolerance, through the Upin & Ipin cartoon film there is moral development in children, teaching positive values ​​that are useful in everyday life. The research method used was a single subject quantitative experimental method, the data collection technique was observation, documentation. The results of this research show that the influence of the Upin & Ipin cartoon film on morale in children aged 5-6 years at Tunas Jaya Kindergarten has a positive impact on children. There is a positive impact on children after watching the Upin & Ipin cartoon film. Children are more knowledgeable. Have a good attitude. Moral development. Cooperation, mutual help, saving, keeping the environment clean. Children imitate the attitudes found in the Upin & Ipin cartoon series. Children will model what the child sees.